Puyŏ and Han: Morphological and Lexical Analysis of Two Distinct Language Groups of the Early Korean Peninsula - Andrew Eric Shimunek (Acta Linguistica Asiatica)
There were many different languages spoken on the Korean Peninsula in the past, and not all of them were 韓 Han (Koreanic). In the traditional approach, Puyŏ and Han – the two best attested non-Chinese languages of early Korea – are treated as daughter branches of a common Puyŏ-Han proto-language. Christopher I. Beckwith has solidly demonstrated that the Puyŏ or Puyo-Koguryoic languages form a unique branch of the Japanese-Koguryoic language family, unrelated to the Han or Koreanic languages. Nevertheless, speculation on Puyŏ-Han linguistic unity continues to persist. The comparative data in this paper, focusing on the earliest attested Puyo-Koguryoic grammatical morphemes and content words and their translational equivalents in early Han (Koreanic), thoroughly disproves the Puyŏ-Han hypothesis, demonstrating that Puyŏ (Puyo-Koguryoic) and Han (Koreanic) are two mutually distinct unrelated language groups.